Model of Religious Study and Moral Values in TK Putra Harapan Nalumsari Jepara - Mubasyaroh Mubasyaroh (Ta'dib: Jurnal Pendidikan Islam, 2016)
Religious and moral education from an early age so needs to be invested for the child, so that in the future they will have a strong and deep understanding of the norms and teachings of Islam. Age children early childhood and kindergarten (TK) is a time to play, so education is implemented particularly religious education should be designed properly by the teacher so that the education process into an active and fun activities. Kindergarten (TK) Putra Harapan Nalumsari Jepara is one of the educational institutions that provide education for early childhood, with one lesson material is a moral and religious education. Moral education is one of the materials is very important because in load values, morals and religion, so this will be a guide for students in later life. The research method used is descriptive qualitative research to describe in detail the subjects and issues to be studied. The findings in this study is the cultivation of religious values and morals for children Kindergarten revolves around the activities of daily life. In particular cultivation of religious values with laying the foundations of the faith, personality or character that is commendable and devotional practices, in accordance with the child's ability is implemented. As one of the early childhood education institutions, in conducting the study, have several models of delivery Edutainment, habituation and uswah hasanah as a reference implementation of teaching and learning.Pendidikan agama dan moral sejak usia dini perlu ditanamkan bagi anak, sehingga di masa depan mereka akan memiliki pemahaman yang kuat dan mendalam dari norma-norma dan ajaran Islam. Usia anak-anak usia dini dan taman kanak-kanak (TK) adalah waktu untuk bermain, sehingga pendidikan diimplementasikan khususnya pendidikan agama harus dirancang dengan baik oleh guru sehingga proses pendidikan menjadi kegiatan yang aktif dan menyenangkan. TK (TK) Putra Harapan Nalumsari Jepara merupakan salah satu lembaga pendidikan yang memberikan pendidikan bagi anak usia dini, dengan satu bahan pelajaran adalah pendidikan moral dan agama. pendidikan moral adalah salah satu bahan yang sangat penting karena di nilai beban, moral dan agama, jadi ini akan menjadi panduan bagi siswa di kemudian hari. Metode penelitian yang digunakan adalah penelitian deskriptif kualitatif untuk menjelaskan secara rinci subyek dan isu-isu yang akan diteliti. Temuan dalam penelitian ini adalah penanaman nilai-nilai dan moral agama untuk anak-anak TK berkisar pada aktivitas kehidupan sehari-hari. Dalam budidaya tertentu nilai-nilai agama dengan meletakkan dasar-dasar iman, kepribadian atau karakter yang praktek terpuji dan kebaktian, diimplementasikan sesuai dengan kemampuan anak. Sebagai salah satu lembaga pendidikan anak usia dini, dalam melakukan pendidikan, memiliki beberapa model pengantar Edutainment, pembiasaan dan uswah hasanah sebagai acuan pelaksanaan belajar mengajar.